Kreativitas Guru Sejarah Kebudayaan Islam Dalam Mengembangkan Media Pembelajaran di MIN 12 Kota Medan - Aminah, Fitria; Rustam, Rustam (Kamaya: Jurnal Ilmu Agama, 2025)
The purpose of this study is to analyze the creativity of Islamic Cultural History (SKI) teachers in developing learning media in MIN 12 Medan City. This study uses a qualitative method with a field study approach, involving 1 SKI teacher and 10 4th grade students as informants. The data collection techniques used were interviews, observations, and documentation, with data analysis using the Miles and Huberman models. The results of the study showed that SKI teachers used various visual and audiovisual media, such as comics, images, animated videos, and PPTs. The development of this media is based on research on student needs and ideas derived from social media, peers, and training. Teachers modify media by simplifying the display, breaking down the material into small sections, and adding interactive elements like quizzes. The effectiveness of the use of this media is evident from the increase in student participation, interest, and understanding of SKI materials, even though teachers face obstacles such as limited time and infrastructure. In conclusion, the creativity of SKI teachers at MIN 12 Medan City plays an important role in creating innovative and effective learning, which can be a reference for other educators.